(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Description of the current state of knowledge about hand, foot, and mouth disease prevention among mothers with children under 5 years old in Ha Long city (formerly), Quang Ninh province, in 2024. Subjects and methods: A cross-sectional descriptive study was conducted on 418 mothers with children under 5 years old from February to August 2024. Data collection was conducted through direct interviews with the study participants using a questionnaire. This questionnaire was developed based on the study’s objectives and content, with reference to the KAP survey tools of previous studies. Results: 76.6% of mothers have adequate knowledge about preventing hand, foot, and mouth disease, while 23.4% have insufficient knowledge. The highest percentage of mothers with sufficient knowledge was in Ha Phong ward at 88%, while the lowest percentage was in Hong Ha ward at 60.2%. Conclusion: The percentage of mothers with children under 5 years old in Ha Long city with correct knowledge about preventing hand, foot, and mouth disease was quite high at. However, there are still many limitations, so intervention programs are needed to improve mothers’ knowledge of disease prevention and childcare.